The impact of long-term exercise intervention on heart rate variability indices: a systematic meta-analysis - Zhang, Wenxin; Bi, Siyuan; Luo, Lin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart rate variability (HRV) is a critical indicator for assessing autonomic nervous system (ANS) function and is closely associated with both cardiovascular and psychological health. Although previous studies have demonstrated that exercise interventions can improve HRV, their effects vary considerably depending on exercise type, intervention characteristics, and individual differences. This meta-analysis aims to evaluate the impact of long-term exercise interventions on HRV and to explore potential factors that influence these effects.MethodsA systematic search was conducted in PubMed, Cochrane Library, EBSCO, CINAHL, Web of Science, and Embase up to November 20, 2024, to identify randomized controlled trials (RCTs) examining the effects of long-term exercise interventions on HRV. Studies involving short-term interventions, non-original research, or incomplete data were excluded. Two researchers independently performed data extraction and quality assessment. In total, 34 studies involving 1,434 participants were included.ResultsLong-term exercise interventions significantly reduced the LF/HF ratio (P < 0.05). Subgroup analyses indicated that the intervention effects were more pronounced in populations with existing health conditions and in interventions lasting ≥8 weeks. Aerobic training and resistance training demonstrated significant benefits.ConclusionLong-term exercise interventions significantly reduce the LF/HF ratio and improve ANS balance. These effects, however, are influenced by individual health status, intervention design, and control group conditions. The high heterogeneity among the included studies and limited data on certain intervention characteristics warrant cautious interpretation of the findings. Future research should focus on conducting more high-quality RCTs to validate these results.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, PROSPERO CRD42024541380.